Algorithm for Multi-Channel Robotic Device Control Based on Minimizing Bayesian Risk - Voznenko, Timofei I.; Kudryavtsev, Konstantin Y. (Procedia computer science, 2021)
Currently, mobile robotic devices are widely used in various fields of human activity, which imposes high requirements on the reliability of their operation. Improving the reliability and quality of control of mobile robotic devices is possible through the use of multi-channel control systems. Signals coming from different control channels are subject to various interference, which can lead to wrong decisions. In this regard, the problem of minimizing the risk of making an incorrect control decision is urgent. This paper gives a theoretical justification for the algorithm for choosing a control command for a multi-channel control system of a mobile robotic device. The algorithm is based on minimizing the Bayesian risk of choosing an erroneous command. To implement the algorithm, it is necessary to have statistical information about the quality of functioning of each control channel.